how do you solve 6x+8y=-50 and 2x-3y=6 while using elimination?

Guest Mar 2, 2017

edited by
Guest
Mar 2, 2017

#1**0 **

So, you take one of the variables and get it on the side of the equals sign that doesn't have a variable yet using opposite symbols. Eg, 2x-3y=6 to 2x=6+3y

I honestly can't remember what next-- I'm in 8th grade math too, but that section was a while ago for me.

Oh oh oh oh oh I REMEMBER

Then when you have 2x=6+3y

then

x=3+3y

Nope. Must've done something wrong.

Sorry. I can't remember ANYTHING.... good luck

raindropsfurrever
Mar 2, 2017

#2**0 **

ERMAHGERD I JUST FOUND MY OLD NOTES ON IT

Say you have

3x -2y=1

+2x +2y=4 (you choose to eliminate one of the variables, in this case, the -2y, so you eliminate it by adding 2y, and then you have to add two across the equation. Granted, I don't know where the 4 came from that)

So now you have

5x=5

x=1

Then, you just check your answer! (By substituting the 1 for the x in the original equation)

2(1)+2y=4

2+2y=4

2y=2

y=1

Vwala!!!!

raindropsfurrever
Mar 2, 2017